A functioning Björk–Shiley aortic valve after 36 years without anticoagulation. Issue 2 (9th February 2023) - Helms, Florian; Rosebrock, Frauke; Haverich, Axel; Rustum, Saad
Abstract: There is a broad consensus among all clinical guidelines that lifelong oral anticoagulation is mandatory after mechanical valve prosthesis implantation. However, in rare cases, patients do not receive anticoagulation or anticoagulation therapy is withdrawn over time. We present a case of an exceptionally durable Björk–Shiley mechanical aortic valve prosthesis still functioning 49 years after implantation. Remarkably, the patient did not receive any anticoagulation or antiplatelet therapy for the first 36 years after implantation. Despite this, no thromboembolic or valve-related adverse events occurred to date. Upon thorough echocardiographic assessment, excellent valve function with a mean transvalvular gradient of 13 mmHg and no prosthetic valve insufficiency was found. This makes the case presented here one of the longest functioning mechanical valve replacements reported. Abstract : The Björk–Shiley (BS) mechanical prosthesis was introduced in 1969 as the first tilting disc valve prosthesis [1].